Analisis Rasio Likuiditas dan Solvabilitas terhadap Kinerja Perbankan Umum yang Go Public di BEI (Studi Kasus pada Perbankan Umum Go Publik yang terdaftar di BEI Periode 2013-2015) - Mayangsari, Retno Duwi, Kusdiyanto, S.E., M.Si (2017)
The purpose of this researchis to analyze the influence of the liquidity ratio and solvency ratio of the financial performance and to determine which of the variable liquidity ratio and solvency ratio has dominant influence on the financial performance. The data used in this research is secondary data of quantitative data. Source of data is originated from 28go public commercial banks listed on the Indonesia Stock Exchange 2013-2015. Analysis of the data is using the liquidity and solvency ratios that include Cash Ratio (CR), Capital Adequacy Ratio (CAR) and Primary Ratio. Classic assumption test which includes multicorrelation test, autocorrelation test and heterokedasity test. Hypothesis test using multiple linear regression test. This test includes t-test, F and coefficientof determination (R2). Based on regression analysis of liquidity ratio and solvency ratio of the variable cash ratio (X1), capital adequacy rati0 (X2) and primary ratio (X3) contributed positively in improving financial performance (Y). liquidity ratio and solvency ratio has a significant influence on the financial performance. Cash ratio (X1) has a dominant influence on the financial performance.